THE EFFECT OF 17% ETHYLENEDIAMINETETRA-ACETIC ACID AS A MAIN IRRIGATION ON APICAL ROOT CANAL CLEANLINESS (ex vivo) - Fibryanto, Eko (Odonto : Dental Journal, 2020)
Background: The root canal wall becomes coated with a smear layer predominantly composed of organic and inorganic matter, debris and bacteria during root canal instrumentation. Sodium hypochlorite (NaOCl) and ethylenediaminetetra-acetic acid (EDTA) are effective in removing the smear layer and they perform as lubricants during root canals instrumentation. The aim of this study was to analyze the efficacy of NaOCl and EDTA as lubricant during root canal preparation on apical third of root-canal wall.Method: Thirty-two premolars were all decoronated. All samples were randomly divided into 2 groups. All groups were instrumented with rotary instrument from #10.04 to #35.04 file. One group was irrigated with 17% EDTA and the other with 5.25% NaOCl. Then the teeth were dried, split into 2 halves and evaluated by 2 examiners under scanning electron microscopy (SEM) at the apical third of the root-canal wall at 1000x magnifications. Data was statistically analyzed using Mann-Whitney test.Result: The result showed that 17% EDTA produced significantly higher cleanliness on apical third of root-canal wall compared to 5.25% NaOCl (p < 0.05).Conclusion: EDTA 17% was able to clean apical third of root-canal wall better than NaOCl 5,25%.